Describing self-care in Italian adults with heart failure and identifying determinants of poor self-care. (April 2015) - Cocchieri, Antonello; Riegel, Barbara; D'Agostino, Fabio; Rocco, Gennaro; Fida, Roberta; Alvaro, Rosaria; Vellone, Ercole
Background: Self-care improves outcomes in patients with heart failure; however, no studies have been conducted on this topic in Italy. Aims: We aimed to describe self-care in Italian adults with heart failure and to identify sociodemographic and clinical determinants of self-care. Methods: A cross-sectional design was used to study 1192 heart failure patients enrolled across Italy. We measured self-care using the Self-Care of Heart Failure Index version 6.2, which measures self-care maintenance, management and confidence. Sociodemographic and clinical data were tested as potential determinants of self-care. Results: The mean age of the sample was 72 (SD = 11) years; 58% were male. In the three areas of self-care, scores ranged from 53.18 to 55.26 and few people were adequate in self-care (14.5% to 24.4% of the sample). Self-care behaviours particularly low in this population were symptom monitoring, exercise, use of reminders to take medicines and symptom recognition. Confidence in the ability to keep oneself free of symptoms and relieve symptoms was low. Taking fewer medications, poor cognition, older age, having a caregiver, being male and having heart failure for a shorter time predicted poor self-care maintenance. Poor cognition, not being employed, being male, and having worse New York Heart Association class predicted poor self-care management. Poor cognition, taking fewer mediations, older age, and male gender predicted poor self-care confidence. Conclusion: Self-care is poor in Italian heart failure patients. Determinants of poor self-care identified in this study can help to target patients' education. Male gender and poor cognition were consistently associated with poor self-care maintenance, management and confidence.